Grado de relación entre diámetro y altura comercial en las plantas de Tetrastilydium peruvianum Sleumer “huacapu negro” por tipo de muestra. Arboretum “el huayo”, Loreto, Perú – 2023 - Espinoza Macayo, Anghel Jhanely (2025)
The objective of the research was to analyze the relationship between diameter and merchantable height in Tetrastylidium peruvianum Sleumer, commonly known as "huacapú negro," within a natural forest, using different sampling methods. The study evaluated trees of the species with a diameter at breast height (DBH) equal to or greater than 10 cm. Various sampling techniques were applied, including Sample 1 (M1), which grouped individuals into diameter classes with a 3 cm amplitude; Sample 2 (M2), with individuals distributed in diameter classes with a 2 cm amplitude; and Sample 3 (M3), which was a representative sample without diameter class stratification, meaning the data distribution was random. The results show that, for the relationship between diameter and merchantable height in Tetrastylidium peruvianum Sleumer in natural forest conditions, the cubic allometric model provided the best fit across all three sampling methods. However, Sample 1 demonstrated the strongest relationship, with 84% of the variation in the dependent variable explained by the model. The predictive equation for the diameter–merchantable height relationship is as follows: Y= 12,138 + (-1,027 x t) + (0,060 x t2) + (-0,001 x t3)